Pengaruh Green Human Resources Management, Kepemimpinan Transformasional, dan Komitmen terhadap Kinerja Organisasi - Adisya Poeja Kehista; Dewi Puspaningtyas Faeni; Adi Wibowo Noor Fikri (Studi Ilmu Manajemen dan Organisasi, 2024)
Purpose: To find out how GHRM, Transformational Leadership and Organizational Commitment have an influence on organizational performance mediated by GHRM implementation practicesMethodology: This study uses a quantitative research method. The sample size based on Slovin's estimate at a 95% confidence level is 100 respondents from 200 employees. In this study, a random sampling technique was used. This study uses the Smart PLS 4.0 program and uses analytical methods in the form of descriptive analysis, validity tests, reliability tests, R-square tests, and hypothesis tests.Results: Organizational performance is mediated by GHRM implementation strategies; the GHRM variable has no visible positive impact. Through the practice of GHRM implementation, the transformational leadership variable has a large and beneficial impact on organizational performance. Organizational performance is influenced by three variables, namely organizational commitment, transformational leadership, and GHRM.Conclusions: The GHRM variable does not have a significant effect on organizational performance through the GHRM Implementation Practices. In contrast, Transformational Leadership and Organizational Commitment have a positive and significant impact on organizational performance through the mediation of GHRM Implementation Practices.Limitations: The need to improve GHRM in companies by implementing practices aimed at improving GHRMContribution: This study introduces the concept of GHRM to further demonstrate that sustainable and environmentally friendly HRM practices are essential to improving organizational performance and increasing organizational commitment. Very useful to be applied in a corporate environment.